2018
DOI: 10.1002/ptr.6084
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HSV‐2 infection by pure compounds from Thymus capitatus extract in vitro

Abstract: Thymus capitatus represents 1 of the 5 Tunisian species of the genus Thymus, which has long‐standing use for flavouring and preserving several food products. Its constituents have been reported to endow antimicrobial properties, but little is known about their antiviral activities. The aim of this study was to examine the antiviral activity of pure compounds from the most bioactive inhibitory T. capitatus extract in vitro against herpes simplex virus Type 2 (HSV‐2) infection and to identify their mechanism of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 34 publications
(41 reference statements)
2
23
0
1
Order By: Relevance
“…It was inactive against rhinoviruses but, reduced the influenza A virus-induced cytopathic effect at non-cytotoxic dilutions (0.03-0.33% v/v) in a dosedependent manner. Thyme extract is also known to inhibit herpes simplex virus infections in vitro [47,48] by inactivating the infectivity of the virus [48].…”
Section: Discussionmentioning
confidence: 99%
“…It was inactive against rhinoviruses but, reduced the influenza A virus-induced cytopathic effect at non-cytotoxic dilutions (0.03-0.33% v/v) in a dosedependent manner. Thyme extract is also known to inhibit herpes simplex virus infections in vitro [47,48] by inactivating the infectivity of the virus [48].…”
Section: Discussionmentioning
confidence: 99%
“…Toujani et al [ 71 ] demonstrated T. capitatus activity against HSV-1 and HSV-2 herpes viruses. Ethanol extract (EE) proved to be the most active against both tested viruses.…”
Section: Antiviral Activitymentioning
confidence: 99%
“…The relevant literature have also indicated that carvacrol has an safety and tolerability effect on healthy volunteers through a phaseIclinical trial and possible therapeutic effect on asthmatic patients through a phase II clinical trial in recent years [19,20]. Carvacrol could exert antiviral activity by preventing the death of cells infected with HSV, but the specific mechanism of it against HSV virus has not been reported up to now [21,22]. As a new alternative energy, carvacrol provides a new possibility for the development of HSV treatment and preventive health care drugs with advantages of great source, safety, low toxicity, and nature.…”
Section: Introductionmentioning
confidence: 99%